Evaluación del funcionamiento técnico del horno de fundición de aluminio de la Universidad Politécnica Salesiana, sede Quito, para la mejora en la eficiencia térmica, durante el año 2015. Propuesta de reformas técnicas en el horno. - Toapanta Ramos, Luis Fernando (2016)
In this work a theoretical and experimental analysis of the thermal efficiency of the smelting furnace type crucible of the Salesiana Polytechnic University, in order to improve the thermal efficiency based on improving establish operating parameters of the furnace , is done by proposing a design extracting hot gases and exchanging this energy using a cross flow exchanger. The heat losses due to heat transfer by conduction, convection and radiation through the cylindrical walls of the furnace, these losses are achieved lower covering partially baked. The literature review indicates the scope of the work carried out around the planet, on the methodology to determine the thermal efficiency crucible type furnace. This part of the study the amount of energy needed to melt 45 kg of aluminum, as well as determining power losses by the walls of the furnace and by the combustion process. The economic costs generated by the implementation of each practice within the laboratory analyzes. Furthermore the increased efficiency of the melting process through improving the operational parameters, design of a fume hood of hot gases and heat exchange to another process is proposed. At the end of the investigation it analyzed economically if the proposal is viable or not to implement it.